1976
DOI: 10.1073/pnas.73.10.3599
|View full text |Cite
|
Sign up to set email alerts
|

A potassium ionophore (valinomycin) inhibits lymphocyte proliferation by its effects on the cell membrane.

Abstract: Valinomycin is a depsipeptide antibiotic which selectively translocates potassium across biologic membranes. This potassium ionophore was observed to inhibit phytohemagglutinin-stimulated blastogenesis and proliferation in human lymphocytes. The (2,3). These agents are thought to interact with membrane receptors and act as triggers for cell proliferation through a series of as yet ill-defined steps. More recently, the calcium ionophore (A23187) was also shown to induce lymphocyte proliferation (4). It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…In this regard, it is interesting to note that addition of K' to Na+-free medium (Table 1 in Deutsch and Price, 1982) for the first 3 hours of lectin stimulation completely reversed inhibition of proliferation observed in low (5 mM) K+, Na+-free medium. Similarly, addition of the K + ionophore valinomycin (Daniele and Holian, 1976) inhibits lectininduced proliferation, and this inhibition is reversed by K+ addition such that EK approximates resting P as determined in this paper. These findings suggest that hyperpolarization of the plasma membrane may provide a negative signal.…”
Section: Removal Of Namentioning
confidence: 66%
“…In this regard, it is interesting to note that addition of K' to Na+-free medium (Table 1 in Deutsch and Price, 1982) for the first 3 hours of lectin stimulation completely reversed inhibition of proliferation observed in low (5 mM) K+, Na+-free medium. Similarly, addition of the K + ionophore valinomycin (Daniele and Holian, 1976) inhibits lectininduced proliferation, and this inhibition is reversed by K+ addition such that EK approximates resting P as determined in this paper. These findings suggest that hyperpolarization of the plasma membrane may provide a negative signal.…”
Section: Removal Of Namentioning
confidence: 66%
“…Amphotericin is structurally similar to nystatin and is also known to cause cation leakage; not surprisingly it also induced biofilm formation. In addition, the nonribosomally synthesized peptide gramicidin, which is structurally unrelated to nystatin but whose functionality is also to cause cation leakage, also induced biofilm formation (7)(8)(9). We tested 2 cyclic lipopeptides known to be produced by different strains of B. subtilis: surfactin and iturin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was also suggested that modulation by Con A of the PMN cell surface may first evoke changes in membrane potential and then be followed by metabolic excitation, suggesting that the changes in membrane potential are a key factor in triggering the dramatic changes in metabolism. A similar idea was also postulated in lymphocytes that changes in membrane potential and ion flux at the cell membrane may play an im portant role in mitogen-induced lymphocyte activation (2).…”
mentioning
confidence: 89%